Neurophysiologic Correlates of Preclinical Alzheimer's Disease. (20th December 2022) - Manning, Daniel; Morse, Christie; Northrop, Andrew; Zeng, Victor; Bolo, Nicolas; Shaughnessy, Lynn; Baratono, Sheena; Buss, Stephanie S.; Ozdemir, Recep; Shafi, Mouhsin; Fried, Peter J.
Abstract: Background: Alzheimer's disease (AD) is associated with neurophysiologic changes, including cortical hyperexcitability and reduced long‐term potentiation (LTP)‐like plasticity, that can be investigated using transcranial magnetic stimulation (TMS). AD is preceded by a preclinical phase of beta‐amyloid accumulation without clinical or cognitive symptoms. Our goal is to test the relationship of TMS‐based neurophysiologic markers against established cognitive and MRI‐based measures of preclinical AD. If neurophysiologic changes precede the clinical manifestation of AD, they could serve as prognostic markers and targets for therapeutic interventions to slow its progression. Method: Data was acquired from eight cognitively unimpaired older adults (three females, ages 65‐78 years) as part of an ongoing study (BrightFocus™ Foundation‐A2021288S, IRB#‐2020P000889). Cognition was evaluated with the 5‐item Preclinical Alzheimer's Cognitive Composite (PACC5), which is sensitive to early AD‐associated decline. Global cortical atrophy was assessed from MRI as the mean thickness across the AD Cortical Signature Network (ACSN)—regions showing morphologic changes that precede the clinical manifestation of AD. Cortical excitability was assessed as the average amplitude of TMS‐evoked EEG potentials (TEPs) elicited from TMS to motor cortex, while LTP‐like cortical plasticity was assessed as the change in TEPs following intermittent theta‐burst stimulation (iTBS). The strength of associations between the neurophysiologic, imaging, and cognitive measures were performed using non‐parametric Spearman Rho coefficients. Result: Spearman coefficients revealed a large association between reduced cortical thickness (more atrophy) and worse cognition (Rho=0.71), as expected. Higher excitability (larger TEPs) showed a large association with worse cognition (Rho=‐0.54) and a small association with reduced cortical thickness (Rho=‐0.29). Lower cortical plasticity (smaller change in TEPs post‐iTBS) showed a medium association with worse cognition (Rho=0.46) and a large association with reduced cortical thickness (Rho=0.86). Conclusion: In cognitively unimpaired older adults, TMS‐EEG measures of cortical excitability and LTP‐like plasticity are strongly correlated, respectively, with cognitive and MRI‐based markers of Preclinical AD. These finding suggest cortical hyperexcitability and reduced LTP‐like plasticity, which are present in AD, may occur before its clinical manifestation. If these results are confirmed in a larger cohort with biomarker testing, these markers could help prognosticate the development of AD symptoms and serve as targets for therapeutic intervention.